Current Status of Health Reporting in Nepali Press - Tuladhar, Sabita; Shresta, Khem Raj; Regmi, Nimesh; Shrestha, Ashoke; Ban, Bharat (Bodhi: An Interdisciplinary Journal, 2013)
DOI: http://dx.doi.org/10.3126/bodhi.v6i0.9242 Bodhi Vol.6 2013: 21-35